Adsorption of toxic metals by natural and modified clinoptilolite - Orhan, Yueksel; Kocaoba, Sevgi (WILEY-V C H VERLAG GMBH, 2007)
The chromium, cobalt and lead removal from aqueous solution by natural and modified zeolites was examined by using a batch-type method. Clinoptilolite samples used in this study were supplied from Bigadi, Turkey. All samples were modified with HNO3 or NaOH to improve the adsorption capacity for heavy metals. The removal efficiencies and kinetics of heavy metals such as chromium, cobalt and lead on natural and modified zeolites were determined. The effects of the initial metal concentration on the removal percentage of heavy metal ions were studied. Freundlich and Langmuir isotherm constants and correlation coefficients were found and the equilibrium process was described by the Freundlich isotherm. The adsorption kinetic was tested and then it indicates the process to be diffusion controlled.
Keywords: HEAVY-METALS; AQUEOUS-SOLUTIONS; ACTIVATED CARBON; ION-EXCHANGE; REMOVAL; LEAD; EQUILIBRIUM; ADSORBENTS; ZEOLITES; KINETICS; Chemistry; Environmental Sciences & Ecology